Plan de negocios para producción y comercialización de la ebanistería “Hermanos Congo” en el cantón Quevedo, año 2014 - Congo Martínez, Angélica Lorena (2015)
This business plan was made on the subject of study Joinery "BROTHERS CONGO", from which information was obtained to give fully to the research topic: "Business plan for production and marketing of the woodwork" Brothers Congo "in Canton Quevedo 2015." With the information obtained from the interview with one of the shareholders of the Joinery, customers and employees could tabulate the results, develop the technical study, develop strategies to market and produce within it, facilitating the development of the main conclusions and recommendations. That is why this research project consists of the following chapters: Chapter I contains the contextual framework of the research consists of: the Problem, limitations, scope and importance of the study, the objectives to be achieved during the investigation. Chapter II consists of the theoretical framework that allowed and defines basic terms associated with the topic as well as the foundations that serve as support for research. In Chapter III the methodology used in the research, selection of the population and study sample, type of research, techniques, procedures and tools used are presented….